2022
DOI: 10.1007/s10792-021-02198-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab to treat retinopathy of prematurity in 865 eyes: a study to determine predictors of primary treatment failure and recurrence

Abstract: Purpose: This study aimed To evaluate the rate and risk factors for primary failure and recurrence after intravitreal anti-VEGF injection in retinopathy of prematurity (ROP).Methods: This retrospective study was performed on 865 eyes from 441 patients with retinopathy of prematurity receiving intravitreal Bevacizumab from 2012 to 2019. Medical records of patients were evaluated.Results: Mean gestational age (GA) and birth weight of patients were 28±2 weeks and 1121±312 g, respectively. Thirty-ve eyes (4.04%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The reactivation rate after intravitreal anti-VEGF monotherapy for Zone I has been reported to be between 4% and 14.6%. [28][29][30] Much is not written on the reactivation rate for ROP in the posterior Zone I (Medline search with keywords anti-VEGF, bevacizumab, ranibizumab, and retinopathy of prematurity posterior Zone I). In our cohort, the reactivation rate was high (59.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The reactivation rate after intravitreal anti-VEGF monotherapy for Zone I has been reported to be between 4% and 14.6%. [28][29][30] Much is not written on the reactivation rate for ROP in the posterior Zone I (Medline search with keywords anti-VEGF, bevacizumab, ranibizumab, and retinopathy of prematurity posterior Zone I). In our cohort, the reactivation rate was high (59.3%).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study showed a much lower recurrence rate (4.04%) after IVB injection in ROP cases. This lower recurrence rate might be related to the lower prevalence of Zone I ROP (21.6%) in the sample size [ 8 ]. Although the distribution of the various stages of ROP did not show any statistical difference between the two groups in our study (A-ROP prevalence 76.9% vs. 51.7% in recurrence and complete regression cases, respectively), this statistically insignificant result may be due to the small sample size and more advanced stages of ROP may increase the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we have to take into account that these children are hospitalized due to respiratory problems or other systemic conditions that can worsen retinal hypoxia or ischemia. Premature infants are more prone to other exacerbating conditions, such as infections, and may have more severe forms of retinopathy due to the lower compliance of anti-oxidant metabolic pathways [ 8 ]. With lower oxygen saturation, the rate of mortality increases; with higher oxygen saturation, the rate of ROP increases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation